Conceptualization of safety leadership in Malaysia's manufacturing companies - Chua, Jing Lun (2014)
In the new global economy, workplace safety has become a central issue among companies all over the world. It is becoming difficult to ignore that this trend has also been happening in Malaysia especially the manufacturing sector. The worrying trend can be seen from the increasing number of workplace accident reported by Department of Occupational Safety and Health (DOSH), Malaysia in manufacturing companies. In recent years, researchers have shown an interest in studying the role of safety leadership to reduce workplace accidents. It is found that safety leadership plays a significant role in ensuring a safe and sound workplace. Due to this concern, this paper attempts to provide a conceptualization of safety leadership from the perspective of Malaysia’s manufacturing sector. It is proposed that positive safety leadership leads to reduction of workplace accidents. In response to this matter, it is hypothesized that the higher level of safety leadership will affect the lower level of workplace accidents. A questionnaire from Wu et al. (2008) will be adopted to explain the conceptualization of safety leadership, it is expected that the concept of safety leadership practiced in Malaysia’s manufacturing sector has a similar meaning from the perspective of western researchers.